ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN DI HOTEL EMERSIA BANDAR LAMPUNG - Yuliarti, Andriani; Herlina, Herlina (Jurnal Manajemen Magister Darmajaya, 2018)
The purpose of analyzing customer satisfaction Emersia Hotel Bandar Lampung. The sample used is 100 people using purposive sampling technique. Data analysis method used in this research is Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) by analyzing the importance of customer and performance given by Hotel Emersia Bandar Lampung. The results of the IPA show the attributes that should be prioritized on the cleanliness of the room and the whole room, the services provided in accordance with the promised, the employees are always willing to help customers, employees are always on the spot when needed customers and employees always understand the needs of customers. The index of customer satisfaction on Emersia Bandar Lampung is satisfied with Customer Satisfaction (CSI) of 76.28. Keywords: Customer Satisfaction, Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI)